Aptitude of areas around Rio Doce State Park for the implementation of agroforestry systems based on multi-criteria analysis - Paula, Luiz Gustavo de Souza (2022)
The Long-Term Ecological Research Program (PELD), conducted studies in communities located near Rio Doce State Park that have resulted in several participative scenarios. These results have a spatially explicit model that presents aptitudes of areas around the park for the implementation of agroforestry systems. This model was built with AHP (Analytic Hierarchy Process) multi-criteria analysis method and using geographic information system tools. The result presents locations and sizes of the areas, according to its levels of aptitude for agroforestry plantations that have environmental preservation and income generation as priority. The variables applied for the analysis are: a) Normalized Difference Vegetation Index (NDVI); b) occurrence of Permanent Preservation Areas (APP); c) Land use/cover classification; d) proximity of access roads. The areas which show the highest levels of aptitude total 5.580 hectares.  They have all the good characteristics, according to the analyzed variables: located in rural areas, close to roads, inside Permanent Preservation Areas and low level of vegetation. A large part of these areas are adjacent to the park, mainly, near the border with Municipality of Coronel Fabriciano and Timóteo, both in Minas Gerais state The biggest areas are located by the most important of the region river’s edge. Also, another analysis made by this work considered results outside the Permanent Preservation Areas. In this case, it can be noticed that there is a greater concentration of areas with the highest levels of aptitude in rural zones of the municipalities of Coronel Fabriciano, Ipatinga and Caratinga, in MG state. In the light of all the aspects analyzed, the conclusion is that the models generated can assist future works for the implementation of Agroforestry Systems in the region, giving initial indications about the best areas for plantings.